Peningkatan Keahlian Pembukuan UMKM Kuliner Binaan PT Sinar Sosro Cempaka Putih Jakarta - Lailah Fujianti; Nelyumna; Rafrini Amyulianthy; Athania Mahardiyanti (SULUH: Jurnal Abdimas, 2020)
A suggestion to School From Home during Covid-19 pandemic made learning process at RA Riyadlotul Uqul, Dusun Lowok, less optimally. Online learning takes place in the form of assignments, and those who haven’t gadgets continue to study at school in turn. The purposes of this service activvity is to develop learning media that is suitbale for the pandemic situation in RA Riyadlotul Uqul. The results of discussions with teachers at that school stated that there were threee suitable media to be developed, animated video, relay stick games, and hand puppets, where all produccts were equipped with user manuals book, so that teacher and parents could easily apply them at home. The product development method adopt ADDIE. The result shows that teacher feels helped by the existance of educational media that is developed, as a variation of teaching techniques, and also build good character for students, which guidebook contains the benefits of using developed media. The teacher, as user, gave suggestions that the video should be uploaded on YouTube, and the guidebook has been copied to make it easier for the teacher to distribute it to the parents of students. The hope is that parents can accompany children to learn while playing at their home.